Topical Delivery of Methocarbamol Loaded Nanoemulgel - in vitro Characterization - Sugumaran, Abimanyu; Mathialagan, Vishali (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Methocarbamol is used as skeletal muscle relaxant. Nanoemulgel is currently being developed as a transdermal drug delivery technology because to its nanosized droplets, which provide superior effectiveness with reduced toxicity. Aim: The aim of the study is to prepare and characterize the Methocarbamol loaded nanoemulgel. Materials and Methods: The required quantity of Methocarbamol dissolved in Acconon oil, surfactant and co-surfactant used to prepare nanoemulsion with various ratios using probe sonicator and poured into the prepared carbopal gel with constant stirring. The prepared nanomelgel was characterized for its pH, viscosity, particle size and zeta potential, surface morphology by TEM, drug content and in-vitro Methocarbamol release from developed formulation. Results: The developed NEs formulation exhibited acceptable pH range around 6 to 7, viscosity was in the range of 38.26cps to 45.25cps. The average droplet size of the NE formulations varied from 20.1 to 56.4 nm. There is no much change of droplet size when varying the oil concentration of the NEs. The result of the droplet polydispersity index (PDI) shows the droplets are uniformly distributed. The zeta potential of the formulations ranging from -0.1mV to 0.3mV for NE and NE-Gel respectively. This is due to the presence of the non-ionic surfactant over the droplet. The TEM micrograph of the 10% NEs and NE-Gel appears spherical in nature with drug embedded in the oil droplet. The volume of drug release for 3% Nanoemulsion is 64.28%, 50.78%, 41.78%, 38.57% and 3% Nanoemulgel is 29.57%, 38.25%, 43.71%, 52.39% respectively. Due to higher quantity of oil phase of NE and rigid gel nature the in-vitro resulted in delaying and sustaining in drug release. Conclusion: Hence, we conclude that the developed NE, NE-Gel might be beneficial for the better topical delivery of muscle relaxant.
Keywords: Methocarbamol; Nanoemulsion; Nanoemulgel; Topical Delivery; In-vitro; characterization